2001
DOI: 10.1021/bi002600g
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Acetylhydrolases:  Broad Substrate Specificity and Lipoprotein Binding Does Not Modulate the Catalytic Properties of the Plasma Enzyme

Abstract: Platelet-activating factor acetylhydrolases (PAF-AHs) are a group of enzymes that hydrolyze the sn-2 acetyl ester of PAF (phospholipase A 2 activity) but not phospholipids with two long fatty acyl groups. Our previous studies showed that membrane-bound human plasma PAF-AH (pPAF-AH) accesses its substrate only from the aqueous phase, which raises the possibility that this enzyme can hydrolyze a variety of lipid esters that are partially soluble in the aqueous phase. Here we show that pPAF-AH has broad substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 44 publications
3
45
0
5
Order By: Relevance
“…Treatment with fenofibrates reduced PAF-AH activity associated with small dense LDL and, in some cases, increased the HDL-associated activity (56). We previously reported that HDL-and LDL-associated PAF-AH behave identically in optimized assays designed to measure initial rates of hydrolysis, a finding supported by other studies that used similar assay conditions (13,58). In contrast, when we and FIGURE 3.…”
Section: Discussionsupporting
confidence: 69%
“…Treatment with fenofibrates reduced PAF-AH activity associated with small dense LDL and, in some cases, increased the HDL-associated activity (56). We previously reported that HDL-and LDL-associated PAF-AH behave identically in optimized assays designed to measure initial rates of hydrolysis, a finding supported by other studies that used similar assay conditions (13,58). In contrast, when we and FIGURE 3.…”
Section: Discussionsupporting
confidence: 69%
“…5 Plasma PAF-AH (pPAF-AH) has a relatively broad substrate specificity for phospholipids, and can catalyze and inactivate not only PAF but also PAF-like oxidized lipids. 6 This enzyme activity has been reported to correlate with several inflammatory diseases such as asthma, 7,8 systemic lupus erythematosus 9 and juvenile rheumatoid arthritis. 10 Furthermore, previous reports have revealed that the polymorphism of pPAF-AH gene (PLA2G7) influences its activity.…”
Section: Introductionmentioning
confidence: 98%
“…PAF-AH II is a single 40-kDa polypeptide (23). This isoenzyme recognizes both PAF and acyl analogs of PAF with moderate length sn-2 chains as well as short chain diacylglycerols, triacylglycerols, and acetylated alkanols (24). Ectopic expression reduces cell death triggered by oxidative stress (25,26).…”
mentioning
confidence: 99%
“…Plasma PAF-AH is a 45-kDa monomer secreted into circulation by endothelial and hematopoietic cells (27,28). The enzyme recognizes PAF and PAF analogs with short to medium sn-2 chains including oxidatively cleaved long chain polyunsaturated acyl chains (24). In vitro, recombinant plasma PAF-AH or ectopic expression protects cells from excitotoxicity or hypercholesterolemia (29 -31).…”
mentioning
confidence: 99%